Molecular docking analyses of CYP450 monooxygenases of Tribolium castaneum (Herbst) reveal synergism of quercetin with paraoxon and tetraethyl pyrophosphate: in vivo and in silico studies. Issue 3 (9th May 2020) - Ghaffar, Ammarah; Sehgal, Sheikh Arslan; Fatima, Rida; Batool, Roya; Aimen, Ume; Awan, Sliha; Batool, Sajida; Ahmad, Faheem; Nurulain, Syed M
Abstract: Pest management in stored grain industry is a global issue due to the development of insecticide resistance in stored grain insect pests. Excessive use of insecticides at higher doses poses a serious threat of food contamination and residual toxicity for grain consumers. Since the development of new pesticide incurs heavy costs, identifying an effective synergist can provide a ready and economical tool for controlling resistant pest populations. Therefore, the synergistic property of quercetin with paraoxon and tetraethyl pyrophosphate has been evaluated against the larvae and adults of Tribolium castaneum (Herbst). Comparative molecular docking analyses were carried out to further identify the possible mechanism of synergism. It was observed that quercetin has no insecticidal when applied at the rate of 1.5 and 3.0 mg/g; however, a considerable synergism was observed when applied in combination with paraoxon. The comparative molecular docking analyses of CYP450 monooxygenase (CYP15A1, CYP6BR1, CYP6BK2, CYP6BK3) family were performed with quercetin, paraoxon and tetraethyl pyrophosphate which revealed considerable molecular interactions, predicting the inhibition of CYP450 isoenzyme by all three ligands. The study concludes that quercetin may be an effective synergist for organophosphate pesticides depending upon the dose and type of the compound. In addition, in silico analyses of the structurally diversified organophosphates can effectively differentiate the organophosphates which are synergistic with quercetin.